Islamic Financial Strategy for Furniture Business Development: A SOAR Analysis Approach - Khusnul Khotimah; Aqwa Naser Daulay; Muhammad Ikhsan Harahap (Jurnal Akuntansi dan Keuangan Islam, 2025)
This study aims to design an Islamic financial strategy for the development of the Djaya Tanjung Morawa Furniture business using the SOAR (Strengths, Opportunities, Aspirations, Results) analytical framework. The research is motivated by the declining performance of small-scale furniture enterprises in North Sumatra amid intense competition and the growing use of non-wood materials. Employing a qualitative descriptive approach, data were collected through interviews, observations, and questionnaires to evaluate both internal (IFE) and external (EFE) factors of the business. The SOAR analysis identified that the SR (Strengths–Results) quadrant achieved the highest total score of 3.865, indicating a strong potential for growth and sustainability. The SR strategy emphasizes increasing sales through product diversification, design innovation, and the adoption of e-commerce platforms to expand market reach. It also promotes production cost efficiency by utilizing the artisans’ experience to optimize processes aligned with Islamic financial ethics, focusing not only on profit generation but also on achieving barakah (blessings) and maslahah (public benefit). The study contributes to Islamic business strategy literature by integrating financial stability with Sharia principles of productivity, fairness, and social welfare. The findings are expected to guide micro and small furniture enterprises in formulating growth-oriented, ethical, and sustainable business strategies within the Islamic economic framework. Penelitian ini bertujuan merancang strategi keuangan Islam dalam pengembangan usaha furnitur Djaya Tanjung Morawa dengan menggunakan kerangka analisis SOAR (Strengths, Opportunities, Aspirations, Results). Latar belakang penelitian ini adalah penurunan kinerja usaha kecil sektor furnitur di Sumatera Utara akibat persaingan ketat dan meningkatnya penggunaan bahan non-kayu. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara, observasi, dan kuesioner untuk menganalisis faktor internal (IFE) dan eksternal (EFE) perusahaan. Hasil analisis SOAR menunjukkan bahwa kuadran SR (Strengths–Results) memperoleh skor tertinggi sebesar 3,865, menandakan potensi pertumbuhan dan keberlanjutan yang kuat. Strategi SR menekankan peningkatan penjualan melalui diversifikasi produk, inovasi desain, serta pemanfaatan platform e-commerce untuk memperluas jangkauan pasar. Selain itu, strategi ini mendorong efisiensi biaya produksi dengan mengoptimalkan pengalaman para pengrajin sesuai etika keuangan Islam, berorientasi tidak hanya pada pencapaian laba, tetapi juga keberkahan (barakah) dan kemaslahatan (maslahah). Penelitian ini memberikan kontribusi terhadap literatur strategi bisnis Islam dengan mengintegrasikan stabilitas keuangan dan prinsip syariah yang menekankan produktivitas, keadilan, serta kesejahteraan sosial. Temuan ini diharapkan dapat menjadi acuan bagi pelaku usaha kecil sektor furnitur dalam merumuskan strategi bisnis yang etis, berkelanjutan, dan berorientasi pada pertumbuhan dalam kerangka ekonomi Islam.